Application of indocyanine green-mediated fluorescence molecular imaging technology in liver tumors resection: a systematic review and meta-analysis - Zhu, Gang; Qiu, Xing; Zeng, Longfei; Zou, Zhirui; Yang, Liu; Nie, Shanmao; Wang, Zuanyu; Zhang, Xin; Tang, Jinquan; Pan, Yong; Tang, Shaozhen; Wu, Tao (Frontiers in Oncology, 2023)
Background This meta-analysis was dedicated to evaluating the safety and effectiveness of indocyanine green (ICG) -mediated fluorescence molecular imaging (FMI) technology in liver tumors resection Methods A literature search of PubMed, EMBASE databases Cochrane Library, and Web of Science was performed to identify all clinical controlled studies exploring the effects of fluorescence imaging on liver tumors resection. Quality assessment and data extraction of studies were conducted independently by 3 reviewers. Mean difference (MD) and odds ratio (OR) with 95% confidence interval (CI) were calculated using a fixed-effects or random-effects model. The meta-analysis was performed with RevMan 5.3 software. Results 14 RCTs involving a total of 1227 patients were finally included. The results showed that Fluorescence-assisted liver tumors resection could improve the R0 resection rate (OR=2.63; 95% CI: 1.46~4.73, P=0.001), reduce overall complications (OR=0.66; 95% CI: 0.44~0.97, P=0.04), biliary fistula (OR=0.20; 95% CI: 0.05~0.77, P=0.02), intraoperative blood loss (MD = −70.76, 95% CI: −106.11 to −35.41; p < 0.0001), and shortens hospital stay (MD = −1.41, 95% CI: −1.90 to −0.92; p < 0.00001). There were no significant differences in the incidences of Operative time (MD = −8.68, 95% CI: −18.59 to −1.22; p = 0.09), complications of grade III or above (OR=0.73; 95% CI: 0.43~1.25, P=0.26), liver failure (OR=0.86; 95% CI: 0.39~1.89, P=0.71), and blood transfusion (OR=0.66; 95% CI: 0.42~1.03, P=0.07). Conclusion Current evidence suggests that ICG-mediated FMI technology could enhance the clinical effectiveness of patients with liver tumors resection and is clinically worthy of promotion.